Evaluation of Acute Kidney Injury and Mortality After Intensive Blood Pressure Control in Patients With Intracerebral Hemorrhage. Issue 8 (13th April 2018) - Burgess, L. Goodwin; Goyal, Nitin; Jones, G. Morgan; Khorchid, Yasser; Kerro, Ali; Chapple, Kristina; Tsivgoulis, Georgios; Alexandrov, Andrei V.; Chang, Jason J.
Abstract : Background: We sought to assess the risk of acute kidney injury (AKI) and mortality associated with intensive systolic blood pressure reduction in acute intracerebral hemorrhage. Methods and Results: Patients with acute intracerebral hemorrhage had spontaneous cause and symptom onset within 24 hours. We excluded patients with structural causes, coagulopathy, thrombocytopenia, and preexisting end‐stage renal disease. We defined AKI using the Acute Kidney Injury Network criteria. Chronic kidney disease status was included in risk stratification and was defined by Kidney Disease Outcomes Quality Initiative staging. Maximum systolic blood pressure reduction was defined over a 12‐hour period and dichotomized using receiver operating characteristic curve analysis. Descriptive statistics were done using independent sample t tests, χ 2 tests, and Mann‐Whitney U tests, whereas multivariable logistic regression analysis was used to evaluate for predictors for AKI and mortality. A total of 448 patients with intracerebral hemorrhage met inclusion criteria. Maximum systolic blood pressure reduction was dichotomized to 90 mm Hg and found to increase the risk of AKI in patients with normal renal function (odds ratio, 2.1; 95% confidence interval, 1.19–3.62; P =0.010) and chronic kidney disease (odds ratio, 3.91; 95% confidence interval, 1.26–12.15; P =0.019). The risk of AKI was not significantly different in normal renal function versus chronic kidney disease groups when adjusted for demographics, presentation characteristics, and medications associated with AKI. AKI positively predicted mortality for patients with normal renal function (odds ratio, 2.41; 95% confidence interval, 1.11–5.22; P =0.026) but not for patients with chronic kidney disease (odds ratio, 3.13; 95% confidence interval, 0.65–15.01; P =0.154). Conclusions: These results indicate that intensive systolic blood pressure reduction with a threshold >90 mm Hg in patients with acute intracerebral hemorrhage may be an independent predictor for AKI.